Determinism, Freedom and Sin: Reformed Theological Resources for a Conversation with Neuroscience and Philosophy. (May 2015) - Messer, Neil
This paper engages with one debate in the emerging field of neuroethics. It is sometimes claimed on the strength of neuroscientific research that our actions are causally determined and therefore not truly free, or more modestly that brain structures or processes constrain some choices and actions, raising questions about our moral responsibility for them. I argue that a Reformed account of providence, sin and grace offers an account of causation able to resist hard determinism, reframes concepts of freedom and responsibility, and provides a theological perspective for evaluating medical interventions in brain activity. Thus the paper not only contributes to a neuroethical debate, but also illustrates the capacity of Reformed ethics to respond creatively to novel problems.